JENIS TIKUS DAN ENDOPARASIT CACING DALAM USUS TIKUS DI PASAR RASAMALA KELURAHAN SRONDOL WETAN KECAMATAN BANYUMANIK KOTA SEMARANG - Afifah Dita Setyaningrum (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Rat is a family in Rodentia order which does harm human as an intermediary of various disease caused by contagion agents including parasites worm. The rat which notably habitates in human’s vicinity could be one of the ways for worm-borne illness to transmit. It can be found with ease around a flea-market. The aim of this research was to provide characterization of rats diversity and worm endoparasites it contains in Pasar Rasamala, Kelurahan Srondol Wetan, Kecamatan Banyumanik. This descriptive research is conducted with cross sectional approach. The samples were trapped rats during four days of experiment, using 100 live-traps. Over 24 trapped rats within 6% rate of trap success, this disclosure revealed that there were Rattus tanezumi (58.3 %), Rattus norvegicus (29.2 %), Rattus exulans (8.3 %), dan Bandicota indica (4.2 %). These rats were infected by worm-parasites at 91.67% rate. The endoparasites found were comprised of Hymenolepis nana, nematoda,Trichuris muris, dan Nippostrongylus brasiliensis. Based on its infection, most of rats in Pasar Rasamala were having single infection rather than combined infection. For the next study can study further on the possibility of worm infections in other organs. In addition, it should be studied on the incidence of worm infection in the human population around the Pasar Rasmala.